The Effect of Addition Moringa Leaves (Moringa oleifera) on the Nutritional Content and Sensory Characteristic of Crackers - Maria Liko K Tapun; Kesuma Sayuti; Daimon Syukri (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2021)
The leaves of M oleifera contain high protein and crude fiber. Thus the addition of M oleifera leaves is expected to increase protein levels and crude fiber levels of crackers produced. This study aimed to determine the effect of the addition moringa leaves on the characteristics of crackers and the addition of the moringa leaves to product crackers on characteristics acceptable to panelists based on sensory analysis. This study used a Completely Randomized Design with 5 treatments, that was the addition of leaves A (4%), B (6%), C (8%), D (10%), E (12%), and 3 replications. The data were analyzed using ANOVA and continued with Duncan's New Multiple Range Test (DNMRT) at a significant level of 5%. The results show that the addition of moringa leaves a significant effect on moisture content, protein content, fat content, ash content, carbohydrates, crude fiber, but does not significantly affect on color, aroma, taste, and texture of the crackers. Based on nutritional content and sensory test, the crackers of treatment E (the addition of moringa leaves 12%) with the characteristics moisture content of 4.67%; protein content of 14.18%; fat content of 22.52%; ash content of 1.67%; carbohydrates of 56.96%; crude fiber of 15.50%; calories of 456.42 kcal/100g; the color of 3.43 (neutral); aroma of 3.83 (likes); a taste of 3.17 (neutral); and texture of 3.30 (neutral).